Establishment and Characterization of a Novel Multidrug Resistant Human Ovarian Cancer Cell Line With Heterogenous MRP7 Overexpression - Wang, Jing-Quan; Wu, Zhuo-Xun; Yang, Yuqi; Li, Jin-Sui; Yang, Dong-Hua; Fan, Ying-Fang; Chen, Zhe-Sheng (Frontiers in Oncology, 2021)
Ovarian cancer is one of the leading female malignancies which accounts for the highest mortality rate among gynecologic cancers. Surgical cytoreduction followed by chemotherapy is the mainstay of treatment. However, patients with recurrent ovarian cancer are likely to exhibit resistance to chemotherapy due to reduced sensitivity to chemotherapeutic drugs. Adenosine triphosphate (ATP)-binding cassette (ABC) transporters have been extensively studied as multidrug resistance (MDR) mediators since they are responsible for the efflux of various anticancer drugs. Multidrug resistance protein 7 (MRP7, or ABCC10) was discovered in 2001 and revealed to transport chemotherapeutic drugs. Till now, only limited knowledge was obtained regarding its roles in ovarian cancer. In this study, we established an MRP7-overexpressing ovarian cancer cell line SKOV3/MRP7 via transfecting recombinant MRP7 plasmids. The SKOV3/MRP7 cell line was resistant to multiple anticancer drugs including paclitaxel, docetaxel, vincristine and vinorelbine with a maximum of 8-fold resistance. Biological function of MRP7 protein was further determined by efflux-accumulation assays. Additionally, MTT results showed that the drug resistance of the SKOV3/MRP7 cells was reversed by cepharanthine, a known inhibitor of MRP7. Moreover, we also found that the overexpression of MRP7 enhanced the migration and epithelial-mesenchymal transition (EMT) induction. In conclusion, we established an in vitro model of MDR in ovarian cancer and suggested MRP7 overexpression as the leading mechanism of chemoresistance in this cell line. Our results demonstrated the potential relationship between MRP7 and ovarian cancer MDR.